Natural Agrobacterium Transformants: Recent Results and Some Theoretical Considerations - Chen, Ke; Otten, Léon (Frontiers in Plant Science, 2017)
Agrobacterium rhizogenes causes hairy root growth on a large number of plant species. It does so by transferring specific DNA fragments (T-DNA) from its root-inducing plasmid (pRi) into plant cells. Expression of T-DNA genes leads to abnormal root growth and production of specific metabolites (opines) which are taken up by the bacterium and used for its growth. Recent work has shown that several plant species belonging to different plant families contain T-DNA genes from A. rhizogenes in their genomes. Plants carrying T-DNAs (called cellular T-DNA or cT-DNA) can be considered as natural transformants. Nicotiana, Linaria and Ipomoea species contain different cT-DNAs, originating from different types of A. rhizogenes strains. In the Nicotiana genus, seven different T-DNAs are found, and in the Tomentosae section no less than four successive insertion events took place. In several cases cT-DNA genes were found to be expressed. In some Nicotiana tabacum cultivars the opine synthesis gene TB-mas2’ is expressed in the roots and caused the plant to produce opines. Here we review what is known about natural Agrobacterium transformants, develop a theoretical framework to analyze this unusual phenomenon and provide some outlines for further research.